Checks Crane Hooks - Blatnicky, Miroslav (Manufacturing Technology Journal, 2015)
Paper deals with comparasion of methods for resolving stress state on the example of forged crane hook of selected load. For suitability of the comparasion is necessary to achieve comparable stress values by different methods. Problem of solving of different assignments by different methods is very extensive, and because of it, there is not clear answer, which of methods is universal and so always optimal. Any factors, that enter to the calculation and influence it, is the best way to choose an optimal method for solving of strength problems in mechanics.
Keywords: Crane hook; FEM analysys; Analytical and graphical methods